Analisis Prioritas Pemeliharaan Terpadu Sewaco Dan Komlek KRI Guna Mendukung Readiness Force TNI AL - Apri Setyo Nugroho; Bambang Suharjo; Achmad Faisol (Departemen Teknik Kelautan Universitas Hasanuddin, 2023)
The Indonesian Navy has an obligation to prepare KRIs to always have good operational readiness in technical conditions which include the Sewaco and Komlek fields to support the Operational Readiness Force (ORF), so it is necessary to carry out effective and efficient maintenance and repair strategies. The purpose of the research is to get the right priority scale of KRI maintenance and repair in the preparation of budget planning for the repair of the Navy Organizational Unit in supporting ORF through the Analytical Hierarchy Process (AHP) approach which considers the criteria of Effective, Efficient and ORF against 5 prioritized alternatives. The results of the study that the preparation of budget planning for the repair of the Navy Organizational Unit is closely related to the use of the state budget, where the KRI Class alternative is the top priority in determining maintenance and repair activities in the sewaco and KRI complex fields in the preparation of budget planning for the repair of the Navy Organizational Unit with a priority value of 0.1826..